Function Analysis of Milk Yield on Small Holder Dairy Cattle in Sumbang Banyumas Region - siswadi, siswadi; subagyo, yusuf; astuti, Triana yuni (ANIMAL PRODUCTION, 2001)
A survey on smallholder dairy cow had conducted in Banyumas region from November 8th 1999 up to February 8th 2000. Forty six respondents were involved in this study (as samples). Cobb - Douglas analysis was applied in this survey. From the study can be concluded that a small holder owned 3.02 heads of dairy cow (2.2 Â ST), 1.44 heads of lactating cow with 9.77 L/day milk production on average. The benefit of the backyard farming was RP.70.603,225 per month on average. Feeding was the biggest influence on benefit because feed cost was 65.81 percent from the production cost. The milk production function , by the equation: Y = 0,8958 X1â°Â·â°Â³Â³Â² X2 0.049 X30.168 X40.608 The four variables can explain 92.4 percent (RÂ²=0,924)on the milkÂ  production variation .It can be suggested that to improve milk production on dairy cows can be done by intensifying labour, and improving the forage feeding. (Animal Production 3(1): 12-19 (2001)Key word: MilkÂ  production ,production function and benefit